Tafsir Kontekstual JIL: Telaah atas Konsep Syariat Islam dan Hudud - Cucu Surahman (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
This article examines the views of Jaringan Islam Liberal (Islamic Liberal Networks) on the concept of Islamic Shari‘ah law, particularly regarding to their interpretation of hudud verses. Through hermeneutical and bibliographical study of several publications and works of JIL, the article concludes that JIL’s interpretations of these issues are very contextual. This can be seen from their use of the historical and rational approach to the Qur’an and its interpratation, as well as from the tendency of subjective and ideological agenda in their support of gender equality, human rights and liberalism.